Islamic land tax = - Katbi, Ghaida Khazna. (London ; New York : I. B. Tauris, in association with the Centre for Arab Unity Studies ; New York : Distributed in the U.S. and Canada exclusively by Palgrave Macmillan, 2010)
Includes bibliographical references (p. [371]-400) and index.